Article RETRACTED due to manipulation by the authors The effect of plyometric training (hurddle jumps), body weight training (lunges) and speed on increasing leg muscle explosive power of futsal players: a factorial experimental design - Ilham Ilham; Anggun Permata Sari; Bafirman Bafirman; Muhamad Sazeli Rifki; Alnedral Alnedral; Wilda Welis; Umar Umar; Randi Kurniawan; Raffiandy Alsyifa Putra; Tri Prasetyo; Bekir Car; Ratko Pavlovic; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Futsal games have high intensity and dynamics that require good skills and physical conditions, one of which is leg muscle explosiveness. By doing plyometric training (hurddle jump), body-weight training (lunges), and paying attention to explosive power factors including speed as a group determinant is believed to affect the explosive power of the player's leg muscles. However, despite recognizing the importance of both training methods in improving leg muscle explosive power, there is still a lack of a thorough understanding of their combined effect on players' leg muscle explosive power during futsal play. This study aims to analyze the differences in the effect of the intervention groups of plyometric training methods and body weight training by considering the level of running speed on explosive power results. Training groups include plyometric training groups and body weight training groups, while speed is categorized as high or low. Using an experimental approach with a 2 x 2 factorial design, this study randomly selected 20 players aged 17.1 ± 0.768 years. Training was conducted in three sessions per week for approximately six weeks. Training focused on fast/explosive movements. Speed data was collected using the 30m acceleration test and the leg muscle explosiveness standing broad jump test. The data were then statistically analyzed using a two-way ANOVA at the 0.05 level of significance. The results showed that both training methods can benefit individuals with high speed (P<0.05). However, leg muscle explosive power training with plyometric exercise was more effective on individuals with high speed (P<0.05). As for those with low speed, plyometric exercise can provide better results (P<0.05). These findings provide valuable insights for futsal coaches and instructors in designing customized training programs to improve leg muscle explosiveness.